AN EMPIRICAL STUDY ON THE ROLE OF INSTAGRAM IN LGBTQ GENDER IDENTITY AND PORTRAYAL - Anannya Mohapatra, Dr. Bhargavi D. Hemmige (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Heterosexuality, in general, is referred to as being 'straight', and is characterized by the societal expectation that men should adhere to masculine traits, while women should embody femininity. Within this framework, individuals of different genders are anticipated to feel a mutual attraction. In societal norms, heterosexuality holds numerical dominance and is largely perceived as a natural orientation. On the contrary, homosexuality, enclosing emotional and sexual attractions between individuals of similar genders, challenges the usual majority norm. This includes cases where males are attracted to males, females to females, or individuals expressing attraction to both sexes. Regrettably, despite increasing acceptance, homosexuality is still sometimes regarded as unnatural within societal contexts. As societal attitudes towards gender and sexual orientation evolve, social media platforms like Instagram have emerged as influential spaces for self-expression and community building within the LGBTQ community. This critical study understands how Instagram is a virtual board for individuals to express, explore, and reconsider their gender identities. However, understanding the complex nature of LGBTQ identity portrayal on Instagram is essential to comprehend how social media is changing and how it is affecting society's views concerning those with different gender orientations. This study adds significant knowledge to the field and will guide future investigations into the relationship between LGBTQ identity, digital platforms, and the wider sociocultural effects of online self-expression. Moreover, this study's empirical data improves our knowledge of how Instagram contributes to the expression and visibility of LGBTQ gender identities in the modern digital era. In a world where social spaces highly shape our basic identity, this research throws light on the multiple roles of Instagram in influencing and reflecting LGBTQ gender identities. As we delve deep into the intersections of technology, identity, and social dynamics, this study aims to contribute valuable insights into the ongoing discussion on LGBTQ representation in the new digital age.